Strength of Polyether Ether Ketone Composite as a Major Connector Material for Removable Partial Dentures - Elsayed, Sherif; Sherief, Dalia Ibrahim; Selim, Mohamed Mohamed; Alian, Ghada Atef (Open Access Macedonian Journal of Medical Sciences, 2022)
PEEK composite was tested mechanically as a maxillary removable partial denture (RPD) framework material instead of cast cobalt chromium alloy. Methods: Partial edentulous upper jaw cast was scanned using structured-light 3D scanner, palatal strap (PS) designs for RPD were designed by a designing dental laboratory software. CAD/CAM machine fabricated PSs patterns using their designs’ STL software files. PSs were made from poly-ether-ether ketone (PEEK) reinforced by ceramic fillers using thermal injection press technique and Co-Cr alloy using centrifugal casting, each material group was subdivided into two subgroups according to storage conditions (stored and non-stored subgroups), storage took place in deionized water for about 180 days at 37.5 ± 2 o C. All specimens were subjected to fracture resistance test using universal testing machine then maximum compression load (MCL) result values were subjected to statistical analysis. PEEK composite specimens were scanned by field emission microscope (FEM) and energy dispersive spectroscopy. Storage water of PEEK composite was analyzed using atomic absorption spectroscopy (AAS). Results: In either stored or non-stored subgroups of PEEK composite straps they showed significant lower mean MCL values than corresponding alloy subgroups (p=0.0001). FEM scanning showed fillers agglomerations in non-stored PEEK composite and their nearly absence from stored PEEK composite specimens. AAS detected Al element in PEEK composite storage water. Conclusion: Mechanically thermally injected ceramic reinforced PEEK composite could not replace cast Co-Cr alloy as PSs material for maxillary RPD. Biocompatibility concerns raised in this study due to suspected Al leaching and ceramic fillers dissolution from PEEK composite matrix.